Recent conventional and exotic charmonia results from LHCb - Kang Youen (EPJ Web of Conferences)
Quarkonia production in heavy-ion collisions is an important experimental probe that sheds light on the heavy quark interaction with the nuclear medium. The bound quarkonium states undergo dissociation and recombination in PbPb collisions, where they can also experience the initial and final state effects such as shadowing and co-mover breakup. With the large datasets of pp and pPb collisions, and excellent vertexing capabilities allowing separation of the prompt and b-decay components, LHCb performs precise measurements of J/ψ, ψ(2S ) and, for the first time at the LHC, χc production and modification in small collision systems. This contribution will discuss these results, along with the first measurement of the nuclear modification factor of the exotic χc1(3872).